Anti-ganglioside Antibodies in Guillain-Barre Syndrome: A Novel Immunoblotting-Panel Assay - Zhu, Jiting; Zhang, Yuanyuan; Li, Runyun; Lin, Yi; Fu, Ying; Yan, Yaping; Zhu, Wenli; Wang, Ning; Zhang, Zaiqiang; Xu, Guorong (Frontiers in Neurology, 2021)
Objective: This study aimed to determine the diagnostic efficiency of a novel immunoblotting detection assay for anti-ganglioside antibodies (AGAs) in Guillain-Barre syndrome(GBS). Method: Serum immunoglobulin (IgG and IgM) of antiganglioside antibodies were measured in 121 participants from a registered cohort study of immune-mediated neuropathies and 29 healthy controls by immunoblotting-panel assay. Assay’s sensitivity, specificity and positive predictive value (PPV) were compared to calculate diagnostic accuracy. Result: In our cohort, any of the antibodies (AGAs) were positive in 42.4% of the GBS patients. The sensitivity and specificity of AGAs (both IgG and IgM) in the diagnosis of GSB were 42% and 76% while for IgG-AGAs were 35% and 87%. AGAs positivity had a signifificant association with the AMAN subtype (P = 0.0004), and the sensitivity, specificity of AGAs in AMAN were 86%, 69%, respectively with high (AUC = 0.78, p = 0.002) discriminative powers. GM1-IgG AGA was more common and specific to AMAN patients than other GBS forms (p = 0.008). Conclusion: Our novel immunoblotting detection assay could complement GBS diagnosis. IgG-AGAs were more likely to be detected in GBS, and GM1-IgG AGA could assist AMAN diagnosis.